A new generalized Bartholdi zeta function for a digraph. Issue 6 (26th April 2021) - Mitsuhashi, Hideo; Morita, Hideaki; Sato, Iwao
Abstract : We define a new generalized Bartholdi zeta function of a digraph D, and give a determinant expression of it. We present a decomposition formula for the new generalized Bartholdi zeta function of a group covering of D . Furthermore, we introduce a new generalized Bartholdi L -function of D, and give a determinant expressions of it. As an application, we present a decomposition formula for the new generalized Bartholdi zeta function of a group covering of D by its new generalized Bartholdi L -functions.